Greek national identity: markers and significations - Στρατουδάκη Χαρά (The Greek Review of Social Research, 2014)
Our research is an attempt to listen to the real subjects of national identity: the silent masses, the «ordinary» members of the nation. Starting from the concept of «markers» of identity, it follows the routes of national identity of teachers of intercultural schools in Attica. Guided by these markers, our research focuses on the ideal and real national self, national time and subjective definitions of nation, to arrive at four different identity narratives, four versions of modern Greek national identity.